Penerapan Metode Hybrid Case Base Pada Sistem Pakar Diagnosa Penyakit Obesitas - Fauzi Erwis; Devri Suherdi; Ardianto Pranata; Asyahri Hadi Nasyuha (STMIK Budi Darma, 2022)
Obesity is a disease that is caused by the condition of a person's body that has a lot of fat in his body and is overweight or very fat. This condition is usually caused by the intake of calories into the human body that exceeds the capacity required by the body, where this condition causes a buildup of calories that turn into saturated fat. These conditions cause various chronic diseases such as diabetes, hypertension and coronary heart disease. Therefore, in order to avoid disease conditions caused by obesity, treatment and knowledge are needed so that it is not too late to take action so that the disease does not become severe. One of them uses an expert system, so that people can check for diseases without having to see a doctor. The method used Hybrid Case Base is used to make the best decision from a number of symptoms or alternatives from the diagnosed disease. The aim is to make it easier for the public to find out the diseases they suffer from obesity and be able to check them early. Where this expert system applies the Hybrid Case Base method which has the final result of this research producing an accurate diagnosis with a sample of symptom data used and getting a similarity measurement percentage of 77% with a diagnosis of the possibility of having Type 2 Diabetes.